A Systematic Review of E-Books in Academic Libraries: Access, Advantages, and Usage. Issue 1 (2nd January 2020) - Blummer, Barbara; Kenton, Jeffrey M.
Abstract: This article presents a systematic review of E-book user studies from 2001 to 2017. It focused on qualitative and quantitative studies that examined academic user groups' attitudes and interactions with E-books. The review aimed to reveal users' knowledge of the E-book format, their ability to define an E-book, their awareness of E-books' availabilities from the institutions' libraries, as well as their appreciation of E-books' advantages. The authors also considered respondents' usage of E-books such as the devices that fostered E-book access, internet avenues individuals' utilized to locate the materials, printing and downloading of E-books, and the time individuals' spent reading E-books online and the frequency of their access. The literature illustrated the importance of E-books to all members of the academic community for research and coursework. Still, studies pointed to a lack of awareness or familiarity among students, faculty, and staff of their institution's E-books especially with the format's features and the various collections owned by the university. To that end, it is especially critical that librarians promote E-books to all potential users.